PARTISIPASI WARGA SEKOLAH TERHADAP PROGRAM ADIWIYATA DI SMA NEGERI 23 BANDUNG - DINAR ISMAILA FAJRIN, - (2022)
Schools that have comfortable conditions can support all components of school equipment to be enthusiastic in their activities. One of the supports in the success of the interaction process between humans and the environment is through Environmental Education. The derivative of Environmental Education is the Adiwiyata program. SMA Negeri 23 Bandung received the Adiwiyata school award at the National level. The Adiwiyata program should make school members take an active role and participate in all activities. In fact, a small number of school components have not shown concern for the environment. Based on this, researchers are interested in conducting research on School Community Participation in the Adiwiyata Program at SMA Negeri 23 Bandung. The objectives of this research are: knowing the form of participation given by school residents in the implementation of the Adiwiyata program at SMA Negeri 23 Bandung, knowing the driving factors in the implementation of the adiwiyata program at SMA Negeri 23 Bandung, knowing the inhibiting factors in implementing the Adiwiyata program at SMA Negeri 23 Bandung. The approach used in this research is qualitative with case study method. The results of the study show that the dominant form of participation in the management of environmentally friendly facilities and infrastructure at SMA Negeri 23 Bandung, the internal awareness of the school to maintain the cleanliness of the school environment is based on policies that are running well to be one of the supporting factors, the inhibiting factor of the program. Adiwiyata requires extra costs outside of routine activities for operationalizing educational activities, there are still a small number of school components that are less concerned about running the Adiwiyata program, in accordance with school policy several relevant subjects have contributed and integrated several topics into subjects.